(untitled) (CIPEEX, 2024)
INTRODUCTION: FEMORAL FRACTURES IN THE ELDERLY POSE A SIGNIFICANT CHALLENGE TO PUBLIC HEALTH. THIS INTEGRATIVE LITERATURE REVIEW SHOWS THAT OLDER PATIENTS WITH PROXIMAL FEMUR FRACTURES FACE NUMEROUS DIFFICULTIES, INCLUDING HIGH MORTALITY RATES, ADVERSE EVENTS, AND LIMITED MOBILITY RECOVERY. ADVANCED AGE AND FRAILTY EMERGE AS SIGNIFICANT RISK FACTORS FOR UNFAVORABLE OUTCOMES, RESULTING IN HIGH MORBIDITY, MORTALITY, AND ASSOCIATED COSTS. FURTHERMORE, MOST OF THESE ELDERLY INDIVIDUALS BECOME INSTITUTIONALIZED, EXPERIENCING SIGNIFICANT MOBILITY LOSS AND DECREASED INDEPENDENCE IN DAILY ACTIVITIES. THE CHOICE BETWEEN SURGICAL AND NON-SURGICAL TREATMENT IS COMPLEX AND INVOLVES MULTIPLE FACTORS, SUCH AS LIFE EXPECTANCY, QUALITY OF LIFE, COSTS, AND PATIENT PREFERENCES. OBJECTIVE: IN THIS PERSPECTIVE, THE AIM OF THIS STUDY IS TO ANALYZE DIFFERENT MANAGEMENT STRATEGIES AND THEIR RESPECTIVE PROGNOSES FOR FEMUR FRACTURES IN ELDERLY PATIENTS. METHODOLOGY: THIS INTEGRATIVE REVIEW WAS CONDUCTED THROUGH SEARCHES IN THE PUBLIC MEDICINE DATABASE AND THE VIRTUAL HEALTH LIBRARY, USING VARIOUS COMBINATIONS OF HEALTH SCIENCE DESCRIPTORS, SUCH AS "FEMORAL FRACTURES," "FRAIL ELDERLY," AND "PROGNOSIS." INCLUSION CRITERIA ENCOMPASSED FREE ORIGINAL ARTICLES PUBLISHED WITHIN THE LAST 5 YEARS AND WRITTEN IN ENGLISH. TEXTS UNRELATED TO THE RESEARCH THEME OR OBJECTIVE WERE EXCLUDED. RESULTS: IT WAS ANALYZED SIX STUDIES RELATED TO THE TREATMENT OF PROXIMAL FEMUR FRACTURES IN ELDERLY AND FRAIL PATIENTS, COVERING VARIOUS CLINICAL ASPECTS, COSTS, AND MULTIDISCIPLINARY CO-MANAGEMENT PROTOCOLS. REGARDING TREATMENT OPTIONS, THE CHOICE BETWEEN SURGICAL AND NON-SURGICAL TREATMENT MUST BE CAREFULLY CONSIDERED. WHILE SURGICAL TREATMENT MAY LEAD TO A SLIGHT IMPROVEMENT IN THE QUALITY OF LIFE, THE ASSOCIATED COSTS ARE SIGNIFICANTLY HIGHER, RAISING QUESTIONS ABOUT COST-EFFECTIVENESS. ADDITIONALLY, THE IMPORTANCE OF SHARED DECISION-MAKING AND THE CAREFUL SELECTION OF PATIENTS ARE EMPHASIZED. THE INVOLVEMENT OF SPECIALISTS IN GERIATRIC CARE IS CRUCIAL IN THE TREATMENT DECISION-MAKING PROCESS. OTHER STUDIES EXPLORED IMPLANT OPTIONS FOR NON-DISPLACED FEMORAL NECK FRACTURES, SUCH AS THE TRIPLE SCREW CONSTRUCT AND DYNAMIC HIP SCREW, WHICH SHOWED SIMILAR PROGNOSES, AND THE FEMORAL NECK SYSTEM, WHICH APPEARED PROMISING IN TERMS OF SURGICAL TIME AND RESISTANCE TO SHEARING FORCES. HOWEVER, ALL TREATMENT METHODS RESULTED IN SOME FRACTURE IMPACTION AND PROXIMAL FEMUR SHORTENING, SUGGESTING THE NEED FOR FURTHER RESEARCH TO CONFIRM THESE FINDINGS. FURTHERMORE, AN OBSERVATIONAL STUDY POINTED TO LOWER MORTALITY RATES IN PATIENTS WITH DISTAL FEMUR FRACTURES WHO UNDERWENT TOTAL KNEE ARTHROPLASTY, ESPECIALLY AMONG YOUNGER PATIENTS. THIS FINDING MAY INFLUENCE TREATMENT APPROACHES IN SPECIFIC CASES. FROM ANOTHER PERSPECTIVE, MULTIDISCIPLINARY CO-MANAGEMENT PROVED EFFECTIVE IN REDUCING THE AVERAGE HOSPITALIZATION TIME, DECREASING INPATIENT MEDICAL EXPENSES, AND REDUCING MORTALITY. HOWEVER, THE LONG-TERM IMPACT ON MEDICAL EXPENSES WAS NOT STATISTICALLY SIGNIFICANT, EMPHASIZING THE NEED FOR ADDITIONAL STUDIES WITH LARGER SAMPLES AND LONGER OBSERVATION PERIODS. CONCLUSION: IN CONCLUSION, THIS INTEGRATIVE REVIEW PROVIDES A COMPREHENSIVE OVERVIEW OF THE CHALLENGES AND TREATMENT OPTIONS FOR ELDERLY PATIENTS WITH PROXIMAL FEMUR FRACTURES. TREATMENT CHOICES SHOULD CONSIDER NOT ONLY CLINICAL OUTCOMES BUT ALSO COSTS, PATIENT PREFERENCES, AND INDIVIDUAL CHARACTERISTICS SUCH AS AGE, FRAILTY, AND LIFE EXPECTANCY. MULTIDISCIPLINARY APPROACHES AND SHARED DECISION-MAKING PLAY A CRUCIAL ROLE IN IMPROVING PROGNOSIS AND MANAGING COSTS RELATED TO THIS TYPE OF INJURY.